Роль Миколаївської морської астрономічної обсерваторії у гідрографічних дослідженнях у Північному Причорномор’ї у першій половині ХІХ ст. - Мітковська, Т.С. (Історичний архів. Наукові студії, 2015)
Висвітлено внесок Миколаївської морської астрономічної обсерваторії у розвиток астрономічної науки та практики, її роль у розвитку гідрографічних досліджень у Північному Причорномор’ї у першій половині ХІХ ст. Узагальнено діяльність Миколаївської морської астрономічної обсерваторії як наукової установи у підготовці офіцерів-гідрографів та як астрономічної бази для Чорноморського флоту. Освещено вклад Николаевской морской астрономической обсерватории в развитие астрономической науки и практики, ее роль в развитии гидрографических исследований в Северном Причерноморье в первой половине
ХІХ в. Обобщена деятельность Николаевской морской астрономической обсерватории как научного учреждения в подготовке офицеров-гидрографов и как астрономической базы для Черноморского флота. The contribution of the Mykolayiv Naval Astronomical Observatory to development of astronomical science and practice, its role in development of hydrographic researches in the Northern Black Sea Coast in the first half of XIX century is described.
Activity of the Mykolayiv Naval Astronomical Observatory as scientific institution for training officers-hydrographers and as astronomical base for the Black Sea Fleet is shown.
The condition of providing Naval Astronomical Observatory with astronomical, navigation devices, tools and special literature at the initial stage of its work is analysed.
Its functions on providing the ships of the Black Sea Fleet with cards and seaworthy tools are described. The contribution of officers-sailors of the Black Sea Fleet under the leadership of the first director of observatory K. Knorre in hydrographic researches of the Black and Azov seas in the first half of the XIX century is shown.